Analysis of legal protection of women's human rights in Indonesia - Sri Devina Hutagalung; Dea Ananda P. Sitompul; Kezia Priskila Sinaga; Sigar P. Berutu; Alendra Alendra (The International Journal of Politics and Sociology Research, 2023)
This research is about the regulation and comparison of the protection of human rights against women in Law Number 23 of 2004 and Law Number 7 of 1984. This research is included in the normative research category, namely research conducted by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The materials are systematically arranged, studied, then a conclusion is drawn in relation to the problem under study. The provisions of Law No. 23 of 2004 concerning the Elimination of Domestic Violence, which regulates the protection of the rights of victims of domestic violence, show that the government has applied the principle of justice by imposing criminal provisions on perpetrators of domestic violence.